Delayed Bilateral Congenital Cataract with Asymmetric Morphology (Membranous and Nuclear) Managed with Different Surgical Techniques in a 19-Year-Old Female: A Case Report - Eva Imelda; Sarra Mutiara Adev; Navneet Shamsundar Toshniwal (Indonesian Journal of Case Reports, 2026)
Congenital cataract is a major cause of preventable childhood blindness, and delayed treatment may lead to irreversible amblyopia and complex lens degeneration. We report a 19-year-old female with long-standing bilateral congenital cataract and marked intra-individual asymmetry. The left eye (OS) had absolute sensory deprivation since infancy, while the right eye (OD) retained partial vision until late adolescence. Examination showed alternating exotropia of 45 prism diopters and intraocular pressures of 18 mmHg OD and 27 mmHg OS. The elevated OS pressure, attributed to secondary lens-induced angle crowding, was controlled to 19 mmHg with topical timolol 0.5%. B-scan ultrasonography confirmed flat, intact retinas and normal optic disc excavation bilaterally. Using SRK/T biometry, staged bilateral cataract surgery was performed under general anesthesia one month apart. OS showed a fully resorbed membranous cataract and required manual irrigation–aspiration with a Simcoe cannula, micro-scissor membranectomy, automated anterior vitrectomy, and sulcus-fixated IOL implantation (20.0 D). OD showed a mature nuclear cataract and was managed with phacoemulsification-assisted irrigation–aspiration and in-the-bag single-piece IOL implantation (22.50 D). Postoperatively, both eyes achieved a clear visual axis and stable IOL position without early complications. At 6 months, IOP remained stable (14 mmHg OD, 15 mmHg OS), with healthy pink optic discs. Corrected visual acuity reached 6/6 OD but remained 2/60 OS due to irreversible deprivation amblyopia. Delayed congenital cataract surgery in adulthood requires morphology-based planning. Nuclear cataracts may be safely treated with phacoemulsification, whereas membranous cataracts require meticulous manual extraction and anterior vitrectomy. Early red-reflex screening remains essential.